MULTIFUNCTIONAL ENVIRONMENT OF UNIVERSITY LIBRARY AS A MOTIVATOR FOR STUDENT SELF-DEPENDENT WORK - Anna A. Pospelova; Rimma R. Tsurtsumia (Высшее образование в России, 2016)
The article discusses the role of university library in providing comfortable conditions for students’ self-dependent work. The experience in creating multifunctional educational environment is described by the example of the reading room of the University library at Tomsk Polytechnic University. Environment multifunctionality is shown at the level of working area, information and librarian. The motivation role of the multifunctionality in the process of extracurricular studies is emphasized.